Handbook of Islamic Education (International Handbooks of Religion and Education,, 2018)
This Handbook traces and presents the fundamentals of Islam and their history and background, and provides a global and holistic, yet, detailed picture of Islamic education around the world. It introduces the reader to the roots and foundations of Islamic education; the responses of Islamic educational institutions to different changes from precolonial times, through the colonial era up to the contemporary situation. It discusses interactions between the state, state-run education and Islamic education, and explores the Islamic educational arrangements existing around the world. The book provides in-depth descriptions and analyses, as well as country case studies representing some 25 countries. The work reflects the recent series of changes and events with respect to Islam and Muslims that have occurred during the past decades. The globalization of Islam as a religion and an ideology, the migration of Muslims into new areas of the globe, and the increasing contacts between Muslims and non-Muslims reinforce the need for mutual understanding. By presenting Islamic education around the world in a comprehensive work, this Handbook contributes to a deeper international understanding of its varieties.